2019
DOI: 10.21873/anticanres.13685
|View full text |Cite
|
Sign up to set email alerts
|

The Normal Epithelium of Crypts Accruing Below Nonpolypoid Adenomas Thrives With Relocated Proliferating Cell-domains and p53-Up-regulated Cells

Abstract: Background/Aim: Colonic crypts with normal epithelium albeit with corrupted shapes (CCS) were previously found beneath nonpolypoid adenomas (NPA). This study aimed to analyze the distribution of proliferating cells (PC) and p53-up-regulated cells in CCS. Materials and Methods: Sections from 48 NPA were immunostained with the proliferating-marker Ki67 and against the tumor-suppressor protein p53. Results: Asymmetric-haphazardly distributed PC were found in 87.5% of the NPA, continuous PC-domains in 8.3%, asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 17 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…50 In another investigation, this time with 48 non-polypoid adenomas, we found that 88% of the CCS exhibited haphazardly asymmetrically-distributed PC-domains, 8% continuous PCdomains in one or both slopes of the CCS, and 4%, asymmetrically-haphazardly distributed single PC. 46 The CCS in 29% of the 48 non-polypoid adenomas also showed p53-upregulated often as single cells. 46 Thus, the CCS accruing beneath the neoplastic tissue of non-polypoid adenomas also thrived with relocated PC-domains and p53 upregulated cells (the latter in nearly one-third of the polypoid adenomas), suggesting cellkinetic alterations and possibly mounting somatic mutations.…”
Section: Non-dysplastic Crypts With Ccs Showingmentioning
confidence: 96%
See 3 more Smart Citations
“…50 In another investigation, this time with 48 non-polypoid adenomas, we found that 88% of the CCS exhibited haphazardly asymmetrically-distributed PC-domains, 8% continuous PCdomains in one or both slopes of the CCS, and 4%, asymmetrically-haphazardly distributed single PC. 46 The CCS in 29% of the 48 non-polypoid adenomas also showed p53-upregulated often as single cells. 46 Thus, the CCS accruing beneath the neoplastic tissue of non-polypoid adenomas also thrived with relocated PC-domains and p53 upregulated cells (the latter in nearly one-third of the polypoid adenomas), suggesting cellkinetic alterations and possibly mounting somatic mutations.…”
Section: Non-dysplastic Crypts With Ccs Showingmentioning
confidence: 96%
“…46 The CCS in 29% of the 48 non-polypoid adenomas also showed p53-upregulated often as single cells. 46 Thus, the CCS accruing beneath the neoplastic tissue of non-polypoid adenomas also thrived with relocated PC-domains and p53 upregulated cells (the latter in nearly one-third of the polypoid adenomas), suggesting cellkinetic alterations and possibly mounting somatic mutations. On the other hand, neither asymmetrically-haphazardly dis-tributed PC-domains, nor p53 upregulated cells were found in any of the more than 200,000 normal colon crypts, including occasional, single CCS in controls.…”
Section: Non-dysplastic Crypts With Ccs Showingmentioning
confidence: 96%
See 2 more Smart Citations
“…p53-Upregulated cells were regarded only those having the same intense immunoreactivity for the p53 tumor-suppressor protein as those in the neoplastic tissue on top. 57 The tumor-suppressor protein p53 was overexpressed in the dysplastic compartment in 39.6% (19/48) of the SNPCoAs. 57 This percentage was somewhat higher than that found in a previous survey at this department, where 25% out of the 433 polypoid conventional adenomas showed p53overexpression in the neoplastic tissue.…”
Section: Biologic Attributes In the Nondysplastic Compartment Of Nonpmentioning
confidence: 99%